Enhancement of carotenogenesis regulated by phosphorylation signaling in the aerial microalga Coelastrella sp. KGU-Y002. (December 2020) - Aburai, Nobuhiro; Tamura, Shun; Abe, Katsuya
Graphical abstract: Highlights: Role of phosphorylation signal in carotenogenesis in aerial microalga was explored. Under nitrogen-deficient condition, JNK inhibitor increased the carotenoid content. EGFR and JAK inhibitors increased the carotenoid accumulation. Broad-phosphatase inhibitors promoted carotenoid accumulation. Abstract: To investigate the roles of phosphorylation signaling toward carotenogenesis in microalgae, we cultured the aerial microalga Coelastrella sp. KGU-Y002 with inhibitors against protein kinase or phosphatase and evaluated carotenoid accumulation using a carotenoid assay. When the algal cells were cultured for 7 days at 60 μmol photons m −2 s −1 in nitrogen-deficient medium with an inhibitor of protein serine/threonine kinase, the c-jun terminal kinase inhibitor increased the carotenoid content to 2.0-fold that in the control. Furthermore, the addition of the inhibitor suppressed algal growth. Incubation with a protein tyrosine kinase inhibitor increased carotenoid accumulation by up to 2.0-fold and did not affect algal growth. Broad inhibitors against protein serine/threonine and tyrosine phosphatase promoted carotenoid accumulation by up to 1.6- and 3.8-fold without suppressing the growth mechanism. Carotenogenesis in microalgae could be enhanced by the general involvement of both phosphorylation and dephosphorylation mechanisms in serine/threonine- and tyrosine-type phosphorylation signaling.